PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS XII IPS.2 SMA NEGERI 13 PALEMBANG - Salmi Salmi (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
This study aims to determine the application of discovery learning learning models to students of class XII IPS.2 Palembang State High School 13. The research used is Classroom Action Research (CAR) or Classroom Action Research (CAR) which aims to improve and findsolutions to real problems in improving the learning process in the classroom. This research has several cycles. Each cycle consists of 4 stages of interrelated and continuous activities, namely: planning (planning), implementation (acting), observation (observing), and reflection (reflecting). The results of the study showed that using the discovery learning model of learning completeness of students before the action and after the action, namely; cycle I (60.00%), and cycle II (90.00%). Thus, it can be concluded that there is a significant change in learning outcomes between before and after being given class action by applying discovery learning learning models to students of class XII IPS.2 Palembang 13 Public High School so that this research is considered to be successful.